CO₂-DRIVEN COLD WATER GEYSERING WELL IN TRANSYLVANIA - BĂILE CHIRUI - Boglárka CZELLECZ; Z. PÁL; D. PETREA; Á. SZÁSZ; L. PALCSU (Studia Universitatis Babeş-Bolyai: Geographia, 2015)
Co2-Driven Cold Water Geysering Well in Transylvania - Băile Chirui. Cold water “geyser” or geysering well is the internationally used term of such phenomenon where cold water is erupting from a hydrogeological well due to CO2 movement. Until now there have been reported 14 geysering wells all over the World (Glennon & Pfaff, 2004). Through this article we would like to add a “new” cold water “geyser” to the above mentioned list, the so called Chirui Geyser. Investigations on Chirui Geyser were carried out several times during 2007 – 2013. Compared with the others, Chirui Geyser has the longest erupting phase with its minimum 38 hours of activity. Switching from the active to the inactive phase or vice versa the values of different parameters of the water are also changing. There has been described an oscillating phase before the water falls back into the pipe. Such activity has not been reported at other cold water geysering wells. Chirui Geyser is located in a post-volcanic area where most probably CO2 has a volcanic origin. In the South Harghita region there are several hydrogeological drillings that reached CO2 rich mineral water aquifers. Many of them could possibly have geysering activity.